#MeToo and Google Inquiries Into Sexual Violence: A Hashtag Campaign Can Sustain Information Seeking - Kaufman, Michelle R. (Journal of interpersonal violence, 2021)
The #MeToo Movement has brought new attention to sexual harassment and assault. While the movement originates with activist Tarana Burke, actor Alyssa Milano used the phrase on Twitter in October 2017 in response to multiple sexual harassment allegations against Hollywood producer Harvey Weinstein. Within 24 hours, 53,000 people tweeted comments and/or shared personal experiences of sexual violence. The study objective was to measure how information seeking via Google searches for sexual harassment and assault changed following Milano’s tweet and whether this change was sustained in spite of celebrity scandals. Weekly Google search inquiries in the United States were downloaded for the terms metoo, sexual assault, sexual harassment, sexual abuse, and rape for January 1, 2017 to July 15, 2018. Seven related news events about perpetrator accusations were considered. Results showed that searches for metoo increased dramatically after the Weinstein accusation and stayed high during subsequent accusations. A small decrease in searches followed, but the number remained very high relative to baseline (the period before the Weinstein accusation). Searches for sexual assault and sexual harassment increased substantially immediately following the Weinstein accusation, stayed high during subsequent accusations, and saw a decline after the accusation of Matt Lauer (talk show host; last event considered). We estimated a 40% to 70% reduction in searches 6 months after the Lauer accusation, though the increase in searches relative to baseline remained statistically significant. For sexual abuse and rape, the number of searches returned close to baseline by 6 months. It appears that the #MeToo movement sparked greater information seeking that was sustained beyond the associated events. Given its recent ubiquitous use in the media and public life, hashtag activism such as #MeToo can be used to draw further attention to the next steps in addressing sexual assault and harassment, moving public web inquiries from information seeking to action.